Improving crop productivity and nitrogen use efficiency using sulfur and zinc-coated urea: A review - Mustafa, Ayesha; Athar, Fareeha; Khan, Imran; Chattha, Muhammad Umer; Nawaz, Muhammad; Shah, Adnan Noor; Mahmood, Athar; Batool, Maria; Aslam, Muhammad Talha; Jaremko, Mariusz; Abdelsalam, Nader R.; Ghareeb, Rehab Y.; et al. (Frontiers in Plant Science, 2022)
Nitrogen (N) is an important macro-nutrient required for crop production and is considered an important commodity for agricultural systems. Urea is a vital source of N that is used widely across the globe to meet crop N requirements. However, N applied in the form of urea is mostly lost in soil, posing serious economic and environmental issues. Therefore, different approaches such as the application of urea coated with different substances are used worldwide to reduce N losses. Urea coating is considered an imperative approach to enhance crop production and reduce the corresponding nitrogen losses along with its impact on the environment. In addition, given the serious food security challenges in meeting the current and future demands for food, the best agricultural management strategy to enhance food production have led to methods that involve coating urea with different nutrients such as sulfur (S) and zinc (Zn). Coated urea has a slow-release mechanism and remains in the soil for a longer period to meet the demand of crop plants and increases nitrogen use efficiency, growth, yield, and grain quality. These nutrient-coated urea reduce nitrogen losses (volatilization, leaching, and N2O) and save the environment from degradation. Sulfur and zinc-coated urea also reduce nutrient deficiencies and have synergetic effects with other macro and micronutrients in the crop. This study discusses the dynamics of sulfur and zinc-coated urea in soil, their impact on crop production, nitrogen use efficiency (NUE), the residual and toxic effects of coated urea, and the constraints of adopting coated fertilizers. Additionally, we also shed light on agronomic and molecular approaches to enhance NUE for better crop productivity to meet food security challenges.